Incidence of acute thermal esophageal injury after atrial fibrillation ablation guided by prespecified ablation index. (30th September 2019) - Halbfass, Philipp; Berkovitz, Artur; Pavlov, Borche; Sonne, Kai; Nentwich, Karin; Ene, Elena; Hoerning, Frank; Barth, Sebastian; Zacher, Michael; Deneke, Thomas
Abstract: Introduction: Ablation index (AI), a novel parameter defining energy application at single ablation lesions, calculated by integration of ablation time, energy, catheter stability, and contact force, has been documented to be associated with effective lesions and higher ablation efficacy. Using a prespecified target AI in addition to acute lesion efficacy may affect local collateral damage like esophageal thermal injury when used for guiding radiofrequency (RF) ablation at the posterior left atrial (LA) wall. Methods and Results: Consecutive patients undergoing first AF ablations using AI were included. Ablation energy was reduced to 25 W when ablating at posterior LA wall. Two different individually defined AI target values were used (300 and 350 for posterior wall ablation). Esophageal endoscopy (EE) was performed 1 to 3 days after ablation procedure to document and categorize endoscopically detected esophageal thermal lesion (EDEL). Two‐hundred and eleven consecutive patients with postprocedural EE were included. Incidence of EDEL was 14% (29 of 211 patients; mild category 1 lesions in 22 of 29 patients (76%) and severe category 2 lesions (ulcers > 5 mm) in 7 of 29 patients (24% of EDEL group, 3% of total group). Ablation time at posterior LA wall (9.5 vs 9.0 minutes [ P = .67]) was comparable in patients with and without EDEL. Conclusion: LA posterior wall RF ablation adopting AI ≤350 was associated with 14% esophageal thermal injury including 3% of severe esophageal thermal ulcers. This incidence is comparable to historic control groups with non AI–guided AF ablation.